IMPLEMENTASI METODE TOTAL PHYSICAL RESPONSE (TPR) UNTUK MENINGKATKAN PENGUASAAN KOSAKATA (VOCABULARY) DALAM MAPEL BAHASA INGGRIS PADA SISWA-SISWI KELAS V MI MIFTAHUL HUDA TUNAH TUBAN - Arjuna Arantisi; Agustin Ningsih, Widji; Novia Ramadhani , Dina Cantika; Dhurrotul Ainiyah, Ziana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery plays a crucial role in the success of English language learning, especially at the elementary education level. Nevertheless, many fifth-grade students at Madrasah Ibtidaiyah still demonstrate limited English vocabulary acquisition, which negatively affects their speaking, reading, and comprehension skills. This problem is mainly caused by the use of conventional teaching approaches that emphasize memorization and teacher-centered instruction, resulting in low student motivation and participation. To address this issue, the Total Physical Response (TPR) method was implemented as an alternative instructional strategy that integrates language learning with physical movement. This study aims to investigate the implementation of the TPR method and to evaluate its effectiveness in improving English vocabulary mastery among fifth-grade students at MI Miftahul Huda Tunah Tuban. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants of this study were fifth-grade students of MI Miftahul Huda Tunah Tuban. Data were collected through classroom observations, vocabulary achievement tests, and documentation. The collected data were analyzed using descriptive qualitative analysis to examine learning activities and quantitative analysis to measure students’ vocabulary improvement. The findings reveal that the application of the TPR method significantly enhanced students’ engagement, motivation, and confidence during the learning process. Furthermore, there was a notable improvement in students’ vocabulary mastery, as evidenced by increased average scores and higher learning mastery percentages in each cycle. These results suggest that the TPR method is an effective and engaging approach for improving English vocabulary mastery in elementary-level students.